Sikap Konsumen Terhadap Pengambilan Keputusan Pembelian Produk Bawang Merah Organik di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia - Oktavianus Wongga; Yoseph Yakob Da Rato; Gabriel Otan Apelabi (Peneliti.net, 2021)
The purchase of organic onion plants by rational consumers will have a positive attitude towards organic plants. Therefore, an understanding of consumer attitudes and decision making towards purchasing organic plants is needed in the garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia. The research was conducted to be able to obtain information about consumer attitudes and decision making in purchasing organic shallots and how much public interest in buying organic shallots with the main problem is how consumers' attitudes towards purchasing decision making for organic shallots in the practice garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia. with the aim of analyzing consumer attitudes towards the attributes of organic shallots in the garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia. This research was conducted in a purposely selected garden of practice at the Faculty of Agriculture, University of Nusa Nipa Indonesia. The research sample of 30 people was selected through accidental sampling. The research data were analyzed descriptively qualitatively and quantitatively using the fishbein multi-attribute model. The results showed that the consumer attitude (Ao) gave the highest value to the resistance of shallots, namely 18.2 and the lowest attribute value of shallot product packaging, namely 7.09.